A STUDY ON EVOLUTION AND STRUCTURE OF INDIAN AUTOMOBILE INDUSTRY - Kamble, Kalpesh S.; Jha, Vinay Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian automobile sector has undergone significant transformations, particularly during the post-liberalization phase that commenced in 1991. This phase marked the opening of the Indian economy to global markets, ushering in technological advancements, foreign direct investment (FDI), and increased competition. This study critically examines the impact of liberalization on the competitiveness of the Indian automobile sector. By analyzing key factors such as market entry of global automobile giants, adoption of modern manufacturing practices, and the role of government policies, the study reveals that liberalization enhanced both domestic and international competitiveness. However, it also exposed the sector to global market volatility and operational challenges. The study further discusses the industry’s transition, highlighting shifts in production standards, consumer preferences, and supply chain efficiencies, all of which contributed to the sector’s resilience and growth.